Combination of inorganic and organic fertilizer in rice plants (Oryza sativa) in screen houses. Issue 1 (March 2021) - Sunarpi, H; Nikmatullah, A; Sunarwidhi, A L; Jihadi, A; Ilhami, B T K; Ambana, Y; Rinaldi, R; Widyastuti, S; Prasedya, E S
Abstract: The demand for agricultural commodities increases from year to year, so farmers also have to increase the production of agricultural products. Farmers can increase agricultural yields through the excessive use of inorganic fertilizers. This causes many problems for the environment, so it is required to reduce the use of inorganic fertilizers in agricultural land. This study aimed to determine the effect of a combination of organic and inorganic fertilizers on the growth and yield of rice. This research was carried out in a screen house in Jatisela, Gunung Sari Subdistrict, Lombok from June to October 2020. The three treatments used in this study were P0 N0 with no organic and inorganic fertilizers; P0 N100 with a dose of 100% inorganic fertilizer and P50 N50 with a dose of 50% organic fertilizer and 50% inorganic fertilizer. The results showed that the combination of organic fertilizers (50%) and inorganic fertilizers (50%) can increase the growth and yield of rice in the screen house compared to control plants and plants which given only 100% inorganic fertilizers. In summary, the combination of organic and inorganic fertilizers can reduce the use of inorganic fertilizers.